A multimodal instrument for real-time in situ study of ultrasound and cavitation mediated drug delivery - Bian, S; Seth, A; Daly, D; Carlisle, R; Stride, E (AIP Publishing, 2017)
The development of a multimodal instrument capable of real-time in situ measurements of cavitation activity and effect in tissue mimicking phantoms during ultrasound and cavitation mediated drug delivery experiments is described here. The instrument features an acoustic arm that can expose phantoms to high-intensity focused-ultrasound while measuring cavitation activity and an optical arm that monitors cavitation effect using confocal microscopy. This combination of modalities allows real-time in situ characterisation of drug delivery in tissue and tissue mimicking phantoms during ultrasound and cavitation mediated drug delivery experiments. A representative result, obtained with a tissue mimicking phantom and acoustically activated droplets, is presented here as a demonstration of the instrument’s capabilities and potential applications.